Microfinance Institution Performance: Does the Macro-economy matter? - Sefa Awaworyi Churchill; Jeffrey Korankye Danso; Elikem Nyatefe (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Microfinance Institutions (MFIs) have been compared at various levels for the purpose of replications and policy formulations. However, the potential effects of the macro-economy on MFI performance are often not considered. We propose that understanding the possible effects of country-level factors on MFI performance can help provide a more accurate evaluation and explain where microfinance fits in the development process. Based on data collected on 563 MFIs, merged with country-level macroeconomic and macro-institutional data, we examine the effects of the macro-economy on MFI performance, specifically, financial and outreach performance as well as default and interest rates. Results suggest that high economic growth is associated with better MFI performance. However, other modes of economic development, including wage-employment opportunities, appear to impede MFI growth, especially outreach growth. Evidence also arises for the rivalry between MFI performance and better institutions. Overall, we find that the success of MFIs depend on macro-economic and institutional factors, although it is likely observed effects may differ by geographical location.
Keywords: 330; microfinance; economic growth; financial performance; sustainability; outreach